URGENSI PELAKSANAAN SUMPAH JABATAN PEGAWAI NEGERI SIPIL DALAM PASAL 1 PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 21 TAHUN 1975 DALAM PERSPEKTIF NEGARA HUKUM DI INDONESIA - Arief Fuady; Evi Deliana; Junaidi Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
ASN actually has a position as an element of the state apparatus, which implements policiesset by the heads of government agencies that are free from the influence and intervention of allpolitical groups and parties. ASN also has a function as a tool for public policy, public servant andunifier of the nation. ASN plays the role of planner, executor and overseer of the implementation ofgeneral government and national development tasks through the implementation of policies and publicservices that are professional, free from political intervention, and clean from corruption, collusionand nepotism practices. Therefore, in order to maintain and strengthen the integrity of civil servants,it is necessary to have an oath of office for civil servants in carrying out their duties and roles. On thebasis of this, it is the author's special interest to conduct further research on the urgency of the oathand its benefits.This research is a normative legal research. This is based on library research which takesquotations from reading books, or supporting books that are related to the problem to be studied.Primary, secondary and tertiary data sources are characteristic of this study. This study also usesqualitative data analysis and produces descriptive data.From the results of the research conducted, there are several conclusions obtained, namely:First, the normative oath of office has no problems in it, the implementation of these norms should becarried out properly by civil servants through work attitudes. With this oath, civil servants arerequired to be more trustworthy in carrying out their positions. Second, there is a juridical implicationfor civil servants when the oath of office is violated. Theoretically normative, civil servants can bedishonorably dismissed if they are proven to have violated the oath, because the oath order hasbecome a norm that has permanent and binding legal force for all civil servants. Therefore, lawenforcement against civil servants who violate their oath of office must be upheld with all theconsequences in an objective and fair manner.Keywords : Oath Of Office-Government Employess